146k views
3 votes
Solve for g 6(−2g−1)=−(13g+2) g =

User Siraj Khan
by
5.9k points

2 Answers

4 votes

Answer:

g = 4

Explanation:

6(-2g - 1) = -(13g + 2)

____________________________________________________________

Distribute,

6(-2g - 1)

-12g - 6

Distribute,

-(13g + 2)

-13g - 2

-12g - 6 = -13g - 2

+13 to both sides,

g - 6 = - 2

Add 6 to both sides,

g = 4

User Smerllo
by
6.5k points
0 votes

Answer:

g = 4

Explanation:

6(−2g−1)=−(13g+2)

Distribute

-12g -6 = -13g -2

Add 13g to each side

-12g + 13g -6 = -13g+13g -2

-6+g =-2

Add 6 to each side

-6+g+6 = -2+6

g = 4

User Baligena
by
6.3k points